(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The technique of mapping continuous speech to the language it belongs to is known as spoken language identification. Front-ends for bilingual voice recognition frameworks, online data retrieval, and automated customer handling in customer support are all examples of spoken language identification applications. The creation of a spoken language recognition system for under-resourced languages of India such as Hindi and Manipuri is presented in this research work. The technology that has been developed is capable of accurately identifying languages. This technology will be used to demonstrate that it is capable of producing superior outcomes. Experimental test runs and evaluation are used to determine if the system is suitable for use in real-time identification scenarios.